Battery pack remanufacturing decisions considering remanufacturing costs and risk priority number in determining repair or replacement - Muqimuddin, Muqimuddin; Pratikno, Faishal Arham; Hertadi, Christopher Davito Prabandewa (Universitas Mercu Buana, 2025)
The growth of electric vehicles is accompanied by an increase in the number of batteries and battery waste produced, which can ultimately have harmful effects on the environment. As a solution, battery pack remanufacturing has emerged as an effective alternative. However, challenges in the remanufacturing process include determining which battery pack components can be repaired and which require replacement with new components, ensuring that remanufacturing costs remain low while preventing potential future failures. This study aims to develop a remanufacturing decision model that integrates Failure Mode and Effect Analysis (FMEA) with a remanufacturing cost model. The study’s results outline the relationship between failure modes and battery pack components, whereby each failure mode can be classified to determine appropriate repair or replacement actions. While specific actions have been formulated, remanufacturing costs remain the final determinant in the overall battery remanufacturing decision. Based on the analysis, repairs or replacement of new part on 13 components associated with failure modes still render the battery pack suitable for remanufacturing, with a potential cost saving of more than 40% compared to purchasing a new battery pack.